Metabolic syndrome prevalence in elderly of urban and rural communities participants in the HIPERDIA in the city of Coimbra/MG, Brazil - Josiane Aparecida Teixeira de Paula; Osvaldo Costa Moreira; Cristiano Diniz da Silva; Diogo Santos Silva; Paulo Roberto dos Santos Amorim (Universidad de Antioquia, 2015)
Objective. To identify the prevalence of metabolic syndrome (MS), and the influence of gender and place of residence for elders served by the Family Health Strategy in the municipality of Coimbra (Minas Gerais state, Brazil). Methodology. The sample consisted of 435 individuals of both sexes, with mean of age 72 ± 8 years. Results. Women had higher prevalence rates of MS (urban= 40%, rural= 37%) with differences (p<0.05, = 0.168 and 0.284) for men (urban= 13%, rural= 22%). Odds Ratio for SM was significant in age groups over 65 years in urban areas, with women having higher chances compared with men (OR=3.07 times), becoming 5.8 times aged 75 to 79 years. Women are more exposed to obesity (urban= 80.4 %, rural= 78.6%) than men, regardless of place of residence (p<0.05, =0.46 and 0.47 respectively), and the urban women are still exposed to hypertension (65%, p= 0.022, = 0.12). Conclusion. The prevalence of MS and exposure to risk factors such as obesity and hypertension was higher in women, mainly in urban areas. Health professionals, like nurses, should note that the elderly population in urban areas have greater exposure to risk factors for MS, which should strengthen educational programs that promote healthy lifestyles.